189k views
2 votes
3(y - 1) +2(y + 3) = 13​

User Lakerskill
by
5.4k points

2 Answers

2 votes

Answer:

y = 2

Explanation:

Although it's rather obvious that we're to solve for y here, you should include those instructions with the problem.

Carrying out the indicated multiplication yields:

3y - 3 + 2y + 6 = 13.

Grouping the y terms, we get 5y on the left side; grouping the constants, we get 10 on the right side.

Dividing both sides of 5y = 10 by 5, we get the final answer, y = 2.

User NewSites
by
6.7k points
3 votes

Answer:

y=2

Explanation:

3(y - 1) +2(y + 3) = 13​

3y-3+2y+6=13

5y+3=13

5y=10

y=2

User Chfw
by
5.7k points